INTERNATIONAL AID AND LOCAL TRANSFORMATION: EXAMINING SOCIAL CHANGE IN POST-EARTHQUAKE TRIENGGADENG-INDONESIA - Teuku Murdani; Usman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Indonesia, situated along the Pacific Ring of Fire, is highly vulnerable to various natural disasters, including floods, landslides, volcanic eruptions, earthquakes, and tsunamis. While the Indonesian government—through BASARNAS—plays a central role in emergency response, international assistance often becomes crucial during post-disaster recovery. This qualitative study, based on interviews, focus group discussions, and field observations conducted across five villages in the Trienggadeng sub-district, Pidie Jaya Regency, Aceh, investigates the social transformations following the 2016 earthquake and the involvement of international aid organizations. The findings reveal a dual impact of aid: it accelerated economic recovery, enhanced infrastructure, and introduced new work ethics and intercultural perspectives. Conversely, it also disrupted traditional communal values, triggered social tensions, fostered dependency, and eroded trust in local governance due to perceptions of favoritism and nepotism. Additionally, while some community members experienced a religious revival, others became more materialistic. This study highlights the complexity of aid-driven recovery and emphasizes the importance of culturally sensitive and participatory approaches to ensure that international assistance supports both physical reconstruction and the preservation of social cohesion.